Evaluasi Pasca Pembangunan Proyek Infra-struktur : Sebuah Kebutuhan Penguatan Kapasitas Birokrat Perencana di Pemerintah Daerah - Budisantoso Wirjodirdjo; Diesta Iva Maftuhah; Iffan Maflahah (LPPM Universitas Trunojoyo Madura, 2021)
Infrastructure development in an area before construction requires preparation and comprehensive initial studies and is an obligation for infrastructure project owners. Likewise, infrastructure development work is completed and operated, post-development evaluation is still needed to avoid unexpected impacts from infrastructure development. It has not been taken into account in the feasibility study. The regions' readiness and role are expected because the areas where the infrastructure is located have an interest and are the areas that are directly affected. However, post-development evaluation of infrastructure is often not carried out properly due to the limited capacity of regional human resources, especially planning bureaucrats in planning infrastructure development and then carrying out post-development evaluations of the infrastructure in their area. Local governments need to initiate capacity building activities for planning bureaucrats and related agencies so that each bureaucrat has a systemic thinking foundation in his work. The second level, local governments cannot work alone to improve the quality of their human resources. Local governments need to greet the nearest tertiary institution with various expertise and contribute this expertise to planning bureaucrats and related technical agencies. Besides, the level II regional government also needs to collaborate with the central government to provide expert assistance regarding post-infrastructure development evaluation.